Common dyadic coping is indirectly related to dietary and exercise adherence via patient and partner diabetes efficacy - Johnson, Matthew D.; Anderson, Jared R.; Walker, Ann; Wilcox, Allison; Lewis, Virginia L.; Robbins, David C. (My University, 2014)
Using cross-sectional data from 117 married couples in which one member is diagnosed with type 2 diabetes, the current study sought to explore a possible indirect association between common dyadic coping and dietary and exercise adherence via the mechanism of patient and spouse reports of diabetes efficacy. Results from the structural equation model analysis indicated common dyadic coping was associated with higher levels of diabetes efficacy for both patients and spouses which, in turn, was then associated with better dietary and exercise adherence for the patient. This model proved a better fit to the data than three plausible alternative models. The bootstrap test of mediation revealed common dyadic coping was indirectly associated with dietary adherence via both patient and spouse diabetes efficacy, but spouse diabetes efficacy was the only mechanism linking common dyadic coping and exercise adherence. This study highlights the importance of exploring the indirect pathways through which general intimate relationship functioning might be associated with type 2 diabetes outcomes.
Keywords: Dyadic coping; Type 2 diabetes; Couple relationship; Dietary adherence; Exercise adherence; Chronic illness